12. ASSOCIATION BETWEEN VOCAL HYGIENE HABITS AND VOICE SYMPTOMS IN PATIENTS VISITING THE OTORHINOLARYNGOLOGY AT MILITARY HOSPITAL 175 (Vietnam Journal of Community Medicine, 2025)
Objective: To assess the association between vocal hygiene habits and voice symptoms in patients visiting the Otorhinolaryngology Department of Military Hospital 175.Subject and methods: A cross-sectional descriptive study was conducted on 113 visitors to the Otorhinolaryngology Department at Military Hospital 175. The survey questionnaire covered aspects related to knowledge and attitudes regarding voice hygiene.Results: The surveyed participants had an average age of 33.75 ± 6.9 years, with a higher proportion of females (60.18%) than males (39.82%). The educational level was relatively high, with 56.64% holding a university degree and 17.7% having postgraduate education. A significant proportion of patients lacked sufficient awareness of harmful vocal habits, such as excessive voice use, alcohol consumption, and smoking.Conclusion: Enhancing patient awareness of vocal hygiene and promoting lifestyle adjustments are essential to reducing the risk of voice-related issues in the community. Implementing health education programs and providing direct counseling at healthcare facilities is necessary to improve patient understanding and encourage behavioral changes.
Keywords: Voice hygiene; knowledge; attitude; otorhinolaryngology disorders.